The Critical Editting of Music: History, Method, and Practice - Grier, James (Cambridge Cambridge University Press, 1996)
This is the first book to provide an introduction to music editing, including the history of the field, and the issues and problems encountered. The preparation of editions for performance and study is one of the most important activities and contributions of the music scholar to cultural life. Through accessible editions, previously unknown music enters the repertoire, while well-known works receive fresh interpretations. Through a series of test cases, James Grier examines music editing from the early music repertoire to contemporary works, including a number of genres from opera to the symphony. Grier also examines the future of music editing and its application on CD-ROM and related electronic media.